1999
DOI: 10.1021/jp983669p
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylate−Counterion Interactions and Changes in These Interactions during Photopolymerization of a Long-Chain Diacetylene Monocarboxylic Acid at Air−Water Interfaces:  External Infrared Reflection Absorption Spectroscopic Study

Abstract: External infrared reflection absorption spectroscopy was used to study the carboxylate-counterion interactions and changes in these interactions during the photopolymerization of a long-chain diacetylene monocarboxylic acid, 10,12-pentacosadiynoic acid (DA), at air-water interfaces in the presence of divalent metal ions, Ba 2+ (pH 7.7), Cd 2+ (pH 6.8), and Pb 2+ (pH 6.0). Upon reducing the molecular area (0.80 f 0.18 nm 2 /molecule), the DA monolayer on each subphase exhibited discrete frequency changes of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 21 publications
(37 reference statements)
6
75
0
Order By: Relevance
“…Monodentate mode of coordination, where only one carbonyl oxygen atom interacts with the metal, due to its lower symmetry than the free ion shows similarities with the spectra of the monomeric form of carboxylic acids. Thus, for monodentate coordination, the asymmetric COO − stretching frequency increases while the symmetric COO − stretch decreases relative to the values observed for free carboxylate ion (Ohe et al 1999). For monovalent silver carboxylates, an opposite effect is observed with a significant lowering of the asymmetric COO − stretching position and generation of Δν as low as 103 cm −1 .…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Monodentate mode of coordination, where only one carbonyl oxygen atom interacts with the metal, due to its lower symmetry than the free ion shows similarities with the spectra of the monomeric form of carboxylic acids. Thus, for monodentate coordination, the asymmetric COO − stretching frequency increases while the symmetric COO − stretch decreases relative to the values observed for free carboxylate ion (Ohe et al 1999). For monovalent silver carboxylates, an opposite effect is observed with a significant lowering of the asymmetric COO − stretching position and generation of Δν as low as 103 cm −1 .…”
Section: Resultsmentioning
confidence: 78%
“…It was found that for bivalent metal cation coordination ability, Δν weakens in the order of monodentate, bridging/ionic bidentate to chelating bidentate form (Ellis et al 2005; Ohe et al 1999). The larger band shift for the complex indicates a larger unsymmetrical interaction between the metal ion and the carboxylate group.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously, the antisymmetric stretching peak of the carboxylate groups was up-shifted to 1614 cm À 1 from 1591 cm À 1 . The invariant Δ value implies that monodentate coordination of copper by the carboxylate moieties was dominant until the equimolar HisC7/ Cu ratio was exceeded; [30] the coordination state changed gradually with further increases in HisC7 content. The peak shifts indicate that not only the imidazole moieties but also the carboxylate moieties coordinated at copper ions.…”
Section: Characterization Of Hisc7[cu] Catalystmentioning
confidence: 99%
“…In addition, referring to the empirical relationship between the frequency difference of the carboxylate stretching bands [13][14][15], that is, Dn ($170 cm À1 ) = n as (COO À )-n s (COO À ) and the types of bonding, the binding state of the carboxylate group to silver in Ag-4NPB is presumed to be a bridging one. Previously, a bridging bond was also assumed for Ag-STA and Ag-4NBA, but the Dn value for Ag-4NBA was 190 cm À1 , while the value for Ag-STA was at best 100 cm À1 .…”
Section: Resultsmentioning
confidence: 99%